Reframing Souths. Ecological Perspectives on the South in Literature, Film, and New Media (Milano University Press, 2025)
The volume offers a multidisciplinary inquiry into the manifold representations of the South(s), approached through an ecocritical and decolonial lens. Edited by Carmen Concilio and Alberto Baracco, the volume gathers contributions from scholars across literature, philosophy, media and visual studies to interrogate the South(s) not simply as a geographic entity, but as a dynamic cultural and epistemological construct. Divided into two sections—respectively devoted to “Literary, Ecocritical, Decolonial, and Comparative Readings” and “Images, Representations, and Visual Cultures”—the volume explores how Souths are imagined, narrated, and visualized across temporal, spatial, and media boundaries. Essays address oceanic and blue humanities, multispecies entanglements, ecological ethics, postcolonial narratives, environmental activism, and visual ecocriticism. Through its wide-ranging and timely perspectives, the volume offers a nuanced exploration of ecocritical concerns, capturing the shifting, dynamic quality of Souths and their role today in postcolonial literature, audiovisual production, and the humanities.